Update on Genetic Conditions Affecting the Skin and the Kidneys - Reimer, Antonia; He, Yinghong; Has, Cristina (Frontiers in Pediatrics, 2018)
Genetic conditions affecting the skin and kidney are clinically and genetically heterogeneous, and target molecular components present in both organs. The molecular pathology involves defects of cell–matrix adhesion, metabolic or signaling pathways, as well as tumor suppressor genes. This article gives a clinically oriented overview of this group of disorders, highlighting entities which have been recently described, as well as the progress made in understanding well-known entities. The genetic bases as well as molecular cell biological mechanisms are described, with therapeutic applications.